How would the equation be exactly transformed given that either a or b or both are negative?
I'd like to stress that this is a hypothetical situation, because in the question we show that b > a > 0.
So let's try the proposed conditions. |a + 3| + |-b| + |b – a| + |ab| = ?
1) b < 0 In this case we can simplify |-b| = -b, because -b > 0. But we can NOT simplify any other absolute value, because we know nothing about a.
2) a < 0 In this case we can NOT simplify any absolute value, because
|a + 3| can be a + 3 (if a is from -3 to 0) OR |a + 3| can be -a – 3 (if a is less than -3)
Any other absolute value contains b and we know nothing about it.
3) a < 0 and b < 0 In this case we can simplify: |-b| = -b, because -b > 0; |ab| = ab, because ab > 0.
We can NOT simplify: |a + 3| for the same reasons as in 2) |b – a| can be b – a (if b > a) |b – a| can be -b + a (if b < a).
You may try to plug some numbers in the absolute values we could NOT simplify: 3) a < 0 and b < 0 a = -1 < 0 , b = -4 < 0 |a + 3| = |-1 + 3| = -1 + 3 = 2 in this case we used |a + 3| = a + 3, because (a = -1 is between -3 and 0) |b – a| = |-4 – (-1)| = -(-4) + (-1) = 3 in this case we used |b – a| = -b + a, because (b = -4 < -1 = a)
a = -4 < 0 , b = -1 < 0 |a + 3| = |-4 + 3| = -(-4) – 3 = 1 in this case we used |a + 3| = -a – 3, because (a = -1 is less than -3) |b – a| = |-1 – (-4)| = -1 – (-4) = 3 in this case we used |b – a| = b – a, because (b = -1 > -4 = a)
Users browsing this forum: No registered users and 3 guests
You cannot post new topics in this forum You cannot reply to topics in this forum You cannot edit your posts in this forum You cannot delete your posts in this forum You cannot post attachments in this forum
GMAT(TM) and GMAT CAT (TM) are registered trademarks of the Graduate Management Admission Council(TM). The Graduate Management Admission Council(TM) does not endorse, nor is affiliated in any way with the owner or any content of this site.